Narrating the Dead in the Anthropocene - Rasmussen, Mikael Schultz (Lagoonscapes)
In the Morning Star series (2020-), Karl Ove Knausgård explores blurred boundaries between life and death, challenging traditional views of mortality. This study uses T. Todorov’s theory of the fantastic and V. Despret’s existentially pluralist philosophy of the dead to examine how the dead in Knausgård’s novels defy binary categorizations. Through narrative techniques e.g. tying and severing of narrative knots, the series creates a space of ambiguity where the dead influence the living, inviting readers to confront questions about reality, agency, and interconnectedness.